2013
DOI: 10.1007/s00701-013-1860-4
|View full text |Cite
|
Sign up to set email alerts
|

Ivy sign, misery perfusion, and asymptomatic moyamoya disease: FLAIR imaging and 15O-gas positron emission tomography

Abstract: Ivy sign on FLAIR imaging is still not rare in patients with moyamoya disease, even when asymptomatic. Although optimal management is still under debate, ivy sign may be an indicator of misery perfusion, and patients with asymptomatic moyamoya disease and ivy sign on FLAIR imaging will benefit from more careful follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
1
25
1
Order By: Relevance
“…Although ivy sign and white matter lesions were not selected in multivariate analysis, the odds ratio revealed high values that were significant. The ivy sign is associated with low cerebral perfusion or misery perfusion [ 37 , 38 ]; therefore, high EPVS might be associated with lower cerebral blood flow. However, this is not true in pediatric cases with moyamoya disease, which can exhibit linear hyperintensities that extend into the perivascular space of the deep white matter in FLAIR imaging [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although ivy sign and white matter lesions were not selected in multivariate analysis, the odds ratio revealed high values that were significant. The ivy sign is associated with low cerebral perfusion or misery perfusion [ 37 , 38 ]; therefore, high EPVS might be associated with lower cerebral blood flow. However, this is not true in pediatric cases with moyamoya disease, which can exhibit linear hyperintensities that extend into the perivascular space of the deep white matter in FLAIR imaging [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,13 Linear hyperintensity along the sulci on fluid-attenuated inversion recovery (FLAIR) imaging is referred to as the "leptomeningeal ivy sign," is considered to indicate retrograde slow flow of the leptomeningeal anastomosis produced by the stenotic or occlusive change in the major vessels, 20 and is indicative of misery perfusion, which is hemodynamic compromise due to impaired cerebral blood flow. 15,24,36 In some pediatric cases, the linear hyperintensity on FLAIR imaging extends to the perivascular space of the deep white matter, 16,20,31,38 is referred to as "medullary streaks," and is considered to be associated with changes in vasculature. 34 The aim of this study was to investigate the characteristics of medullary streaks on FLAIR imaging in pediatric moyamoya disease and to explore the pathophysiology of the findings.…”
mentioning
confidence: 99%
“…20,24,31 By using positron emission tomography, Vuignie et al also found that ivy sign was significantly correlated with the increase OEF. 23 Consistently, the improvement of CVR after direct or indirect bypass surgery brought about a decrease in ivy sign. 19,20,22 Thus, all the above results were considered as critical evidence that the ivy sign originates from slow retrograde flow of engorged pial arteries via leptomeningeal anastomosis compensating for decreased perfusion pressure.…”
Section: Angiographymentioning
confidence: 78%
“…The incidence of ivy sign in MMD on the term "patients" ranged from 30.3% to 100%. However, if we exclude the three studies 23,28,31 that reported incidence less than 40%, the remaining nine studies all reported a very high incidence: more than 80%.…”
Section: Incidencementioning
confidence: 99%